2019
DOI: 10.1016/j.foodqual.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study on acceptance of food textures between 6 and 18 months

Abstract: The timely complementary food introduction is important for the development of healthy eating. However, little evidence is available about when to introduce which texture during this period. This study aims to fill this gap by measuring the evolution of food texture acceptance and feeding behaviours between 6 and 18 months. Two groups of healthy children participated in the study: at 6, 8, and 10 months (n=24) and at 12, 15 and 18 months (n=25), respectively. They were offered foods with different textures (pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 30 publications
5
40
1
Order By: Relevance
“…For aversions to specific food textures, early dietary intervention is important as experience with different textures early in life might facilitate infants' acceptance of more complex textures at a later stage (Blossfeld, Collins, Kiely, & Delahunty, 2007;Demonteil et al, 2018;Demonteil et al, 2019;Johnson, 2016). As such, food texture acceptance is also known to evolve with age; certain textures that are not accepted at one age may be accepted at a different age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For aversions to specific food textures, early dietary intervention is important as experience with different textures early in life might facilitate infants' acceptance of more complex textures at a later stage (Blossfeld, Collins, Kiely, & Delahunty, 2007;Demonteil et al, 2018;Demonteil et al, 2019;Johnson, 2016). As such, food texture acceptance is also known to evolve with age; certain textures that are not accepted at one age may be accepted at a different age.…”
Section: Introductionmentioning
confidence: 99%
“…This decreased masticatory efficiency may be associated with a loss of sensory input, decreasing the pleasurable aspects of eating (Hennequin, Faulks, Veyrune, & Bourdiol, 1999). Struggles with texture sensitivity often persist into adulthood (Hennequin, Allison, Faulks, Orliaguet, & Feine, 2005), highlighting the importance of understanding food texture selectivity and aversion in childhood (Demonteil et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The gel was processed by chewing/biting by all children and by chewing/biting and sucking for half of them. The frequency of sucking behavior observed is higher than observed with real foods (Demonteil et al, 2019). We believe that this behavior can be either induced by the presence of the mesh or favored by possibility to better taste the sweetness of the gel by sucking.…”
Section: Evolution Of Masticatory Performance With Age Relationshimentioning
confidence: 59%
“…This transition in oral processing strategy between 6 and 10 MO is congruent with the strategy naturally adopted by children when eating hard foods. Indeed, we previously studied the same children in eating situations and observed that the probability of eating a biscuit by sucking decreased from 1 to 0.7 between 6 and 10 MO whereas the chewing probability sharply increased from 0.1 to 0.8 during the same period (Demonteil et al, ). A transition from sucking to chewing at an early age of complementary feeding was also reported in another study characterizing 6 and 24 MO children in feeding situations (Gisel, ; Stolovitz & Gisel, ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation